Stabilization of resveratrol in blood circulation by conjugation to mPEG and mPEG-PLA polymers: Investigation of conjugate linker and polymer composition on stability, metabolism, antioxidant activity and pharmacokinetic profile - Siddalingappa, B.; Benson, Heather; Brown, D.; Batty, Kevin; Chen, Y. (Public Library of Science, 2015)
Resveratrol is naturally occurring phytochemical with diverse biological activities such as chemoprevention, anti-inflammatory, anti-cancer, anti-oxidant. But undergoes rapid metabolism in the body (half life 0.13h). Hence Polymer conjugation utilizing different chemical linkers and polymer compositions was investigated for enhanced pharmacokinetic profile of resveratrol. Ester conjugates such as α-methoxy-ω-carboxylic acid poly(ethylene glycol) succinylamide resveratrol (MeO-PEGN-Succ-RSV) (2 and 20 kDa); MeO-PEG succinyl ester resveratrol (MeO-PEGO-Succ-RSV) (2 kDa); α-methoxy poly(ethylene glycol)-co-polylactide succinyl ester resveratrol (MeO-PEG-PLAO-Succ-RSV) (2 and 6.6kDa) were prepared by carbodiimide coupling reactions. Resveratrol-PEG ethers (2 and 5 kDa) were synthesized by alkali-mediated etherification. All polymer conjugates were fully characterized in vitro and the pharmacokinetic profile of selected conjugates was characterized in rats. Buffer and plasma stability of conjugates was dependent on polymer hydrophobicity, aggregation behavior and PEG corona, with MeO-PEG-PLAO-Succ-RSV (2 kDa) showing a 3h half-life in rat plasma in vitro. Polymer conjugates irrespective of linker chemistry protected resveratrol against metabolism in vitro. MeO-PEG-PLAO-Succ-RSV (2 kDa), Resveratrol-PEG ether (2 and 5 kDa) displayed improved pharmacokinetic profiles with significantly higher plasma area under curve (AUC), slower clearance and smaller volume of distribution, compared to resveratrol.